PENGARUH PENGHINDARAN PAJAK TERHADAP KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Hernengsih; Nailufaroh, Lulu (Universitas Serang Raya, 2024)
This research aims to determine the effect of Tax Avoidance on Financial Performance with Good Corporate Governance as a moderating variable. The study employs a quantitative method. The research population consists of 44 companies, and a sample of 13 companies was selected using purposive sampling. The data source used is secondary data in the form of financial statements of manufacturing companies in the consumer goods sector listed on the Indonesian Stock Exchange (IDX) for the period 2019 – 2023, and analyzed using multiple linier regression with SPSS version 27. Based on the research results, it can be concluded that: 1) Tax avoidance has a negative effect on financial performance, and 2) Good Corporate Governance, as proxied by managerial ownership, is unable to moderate the relationship between tax avoidance and financial.